139D in NS1 Contributes to the Virulence of H5N6 Influenza Virus in Mice - Huang, Kun; Mao, Haiying; Ren, Peilei; Zhang, Yufei; Sun, Xiaomei; Zou, Zhong; Jin, Meilin (Frontiers in Veterinary Science, 2022)
H5N6, the highly pathogenic avian influenza A virus (IAV) of clade 2.3.4.4, causes global outbreaks in poultry. H5N6 has become the dominant IAV subtype in waterfowls and causes human infections with high mortality rates. Here, we isolated two strains of H5N6, XGD and JX, from chickens and ducks. Growth ki-netics were evaluated in duck embryo fibroblasts, chicken embryo fibroblasts, Madin-Darby canine kidney cells, and A549 lung carcinoma cells. Receptor binding specificity was analyzed via sialic acid¬–binding ac-tivity assay. The virulence of each strain was tested in BALB/c mice, and recombinant viruses were con-structed via reverse genetics to further analyze the pathogenicity. The two strains showed no significant dif-ferences in growth kinetics in vitro; however, JX was more virulent in mice than XGD. We also identified 13 mutations in six viral proteins of the two strains through genetic analysis. Our study showed that the NS1 protein played a crucial role in enhancing the virulence of JX. Specifically, the amino acid 139D in NS1 con-tributed to the high pathogenicity. Therefore, 139D in NS1 might provide insight into the underlying mecha-nism of IAV adaptation in mammals.